2017
DOI: 10.12973/ejmste/81150
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Academic Mobility of Future Foreign Language Teachers by Means of Media Education Technologies

Abstract: The relevance of research: Modern transformations in society and education pay special attention to the increase of the quality of teaching staff training, making new requests for competitive specialists in the world labor-market. According to the demands of educational laws and regulations, modern teacher is meant to be competent in his own sphere of work, have a number of professional skills, be flexible and mobile, be capable to work efficiently in compliance with international standards, be prepared for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, the respondents with the shortest experience achieved the lowest score, which may indicate less interest in implementing the issue of media education in the teaching process. This result is surprising, especially considering the results of some other research, which showed that the younger teachers were more willing to include elements that brought new methods or forms, thereby contributing to a more attractive lesson (e.g., Bond et al, 2018;O'Bannon & Thomas, 2014;Simmons et al, 2017;Wang et al, 2018). The results could be caused by the factor of longer experience in teaching and thus also greater implementation of media education methods in teaching.…”
Section: Discussionmentioning
confidence: 95%
“…However, the respondents with the shortest experience achieved the lowest score, which may indicate less interest in implementing the issue of media education in the teaching process. This result is surprising, especially considering the results of some other research, which showed that the younger teachers were more willing to include elements that brought new methods or forms, thereby contributing to a more attractive lesson (e.g., Bond et al, 2018;O'Bannon & Thomas, 2014;Simmons et al, 2017;Wang et al, 2018). The results could be caused by the factor of longer experience in teaching and thus also greater implementation of media education methods in teaching.…”
Section: Discussionmentioning
confidence: 95%
“…Theoretical aspects and practical issues of economic development and innovation activity are considered in studies [3][4][5], the problems of higher education economic and innovative development are presented in researches [6][7][8][9][10][11][12][13], innovative development of society is disclosed in a number of studies [14,15], the authors of which prove the close relationship between the country's competitiveness and innovation potential, emphasizing the need to support the country's higher education at the global level.…”
Section: The Objective Of the Workmentioning
confidence: 99%
“…The principal indicator of the security of the medical institutional environment is the ability of this environment, through the opportunities provided, to ensure the satisfaction of the entire hierarchical complex of the participants' needs in educational relations, creating an appropriate motivation for their active's activity. 2 The social security of the medical institutional environment includes the protection of participants in educational relations from destructive personal and physical threats, which allow reducing the risks of development of destructive processes and personal addictions, thereby preventing the emergence of social problems and conflicts [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%